2015
DOI: 10.1371/journal.pone.0133751
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cell Genome Browser: Enabling the Identification of Novel Serum Response Factor Target Genes

Abstract: Genome-scale expression data on the absolute numbers of gene isoforms offers essential clues in cellular functions and biological processes. Smooth muscle cells (SMCs) perform a unique contractile function through expression of specific genes controlled by serum response factor (SRF), a transcription factor that binds to DNA sites known as the CArG boxes. To identify SRF-regulated genes specifically expressed in SMCs, we isolated SMC populations from mouse small intestine and colon, obtained their transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(117 citation statements)
references
References 41 publications
7
110
0
Order By: Relevance
“…In addition, our transcriptome data showed that little or no Elk1 was expressed in both jejunal SMCs and colonic SMCs, whereas Srf was abundantly expressed in a SMC-specific manner. 27 These observations support a model for direct SRF regulation of the GI SMC phenotype during intestinal obstruction, which differs from that of vascular SMCs. Whether expression of SRF and contractile proteins (myosin heavy chains) increases or decreases with intestinal smooth muscle hypertrophy has been the subject of controversy.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, our transcriptome data showed that little or no Elk1 was expressed in both jejunal SMCs and colonic SMCs, whereas Srf was abundantly expressed in a SMC-specific manner. 27 These observations support a model for direct SRF regulation of the GI SMC phenotype during intestinal obstruction, which differs from that of vascular SMCs. Whether expression of SRF and contractile proteins (myosin heavy chains) increases or decreases with intestinal smooth muscle hypertrophy has been the subject of controversy.…”
Section: Discussionsupporting
confidence: 64%
“…22,23 They express as many as 447 ion channel and transporter isoforms, indicating that SMC excitability is regulated by a complex coordinated effort of numerous ion channels and transporters. 10 Within the ion channel family, calcium channels were the most abundantly expressed in SMCs, 10 and the predominance of calcium channel expression is consistent with the current paradigm for excitation-contraction coupling, which is primarily regulated by Ca 2+ via calcium channels. 22 Many highly expressed and SMC-restricted ion channel isoforms and regulators such as Kcnmb1, Ryr3, Jph2, and Dmpk appear to be regulated by SRF.…”
Section: Smooth Muscle Cell Transcriptomesupporting
confidence: 65%
“…10 SMCs express 16 000 genes, which are transcribed into 55 000 transcriptional variants. The most highly expressed genes are related to muscular contraction.…”
Section: Smooth Muscle Cell Transcriptomementioning
confidence: 99%
See 2 more Smart Citations